Penguatan Kesadaran Spiritual dan Sosial melalui Edukasi Partisipatif Qurban Idul Adha 1447 H di SMP Negeri 3 Medan - Yogi Putra (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2026)
The character development of today's kids is beset by a number of issues, including diminishing spiritual awareness, poor social awareness, and waning moral principles in daily life. These circumstances highlight the necessity for educational initiatives that can sustainably incorporate the reinforcement of social and spiritual values. Through interactive instruction on the Eid al-Adha 1447 H sacrifice at SMP Negeri 3 Medan, this community service project seeks to raise students' spiritual and social consciousness. Through interactive counseling, conversations, question and answer sessions, introspection, sacrifice simulations, and activity sharing with others, students are actively involved in the educational process. To find changes in knowledge and attitudes, the activity was evaluated using participant reflections, pre-tests, post-tests, and observation. Students comprehension of the concept of sacrifice, the virtues of sincerity, sacrifice, and social consciousness increased as a consequence of the exercise. Participants also shown more involvement, empathy, solidarity, and awareness to share with underprivileged populations. This exercise demonstrates that sacrifice-based participation education may be a useful tool for enhancing students' social and spiritual character and fostering the growth of community-based character education within the educational setting.